Measuring the Impact of Commitment to Apply Banking Governance Mechanisms (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to measure the impact of applying bank governance mechanisms in reducing the financial risks of banks listed on the Palestine Stock Exchange, and to answer research questions and test hypotheses for the study, researchers adopted the descriptive and analytical approach, and data were collected from the annual financial reports of the banks listed on the Palestine Exchange during the period between (2009-2018), as a time series for the purpose of finding, analyzing and measuring the effect between the study variables during this period by (60) views for each of the study variables, using the statistical analysis program views(9) to enter, process and analyze the data. The results of the study proved that there is a statistically significant effect of bank governance mechanisms on the risks (credit, capital, and liquidity) of the banks listed on the Palestine Exchange. The study recommends the necessity of identifying and measuring financial risks and mitigation measures, reporting and controlling them in the sense of subjecting these risks to governance mechanisms, adopting these procedures to apply appropriate strategies and practical procedures, and preparing the necessary internal measures and data on these risks in proportion to the scope, extent and nature of banks' business.